Yield and bromatological composition of three Brachiaria varities in two areas of Ecuador - Reyes Pérez, J.J.; Méndez Martínez, Y.; Luna Murillo, R. A.; Verdecía, D. M.; Espinoza Coronel, A. L.; Pincay Ronquillo, W.J.; Espinosa Cunuhay, K.A.; Macías Pettao, R. K; Herrera, R.S. (Cuban Journal of Agricultural Science, 2020)
Using a random block design with factorial arrangement (3x2) the effect of the climatic area (Guayas and El Empalme) in the yield components and bromatological composition of three Brachiaria varieties (Decumbens, Brizantha and Mulato I) was studied. The yields of total dry matter, biomass, leaves and stems, the plant height, length and width of leaves, the contents of DM, CP, NDF, ADF, ADL, cellulose (Cel), hemicellulose (Hcel), cellular content (CC), P, Ca, ash, OM, DMD, OMD, ME, NFE and relations leaf/stem, NDF/N and ADF/N were determined. Analysis of variance was performed according to experimental design. There was significant interaction (P <0.0001) between the varieties and the area for some of the studied indicators. The highest yields of total DM, leaves, stems and biomass were obtained in Mulato I in El Empalme (1.32, 0.79, 0.53 and 5.08 t/ha, respectively P<0.001). The CP was better in Mulato I in Guayas (13.08 %, P<0.001), the cell wall components did not showed variety x area interaction, with significant differences in terms of the varieties for NDF, CEL and CC with the highest results for cv. Decumbens and Mulato I (38.21, 17.26 and 64.22 %, respectively P< 0.05). While for the area the highest percentages of ADF and ADL (20.12 and 3.47 %, respectively P< 0.02) were for Guayas. In this research was showed the effect of the climate factors and the variety on the yields and some quality indicators were the best productive and morphological performance in the higher rains area (El Empalme) was obtained, while for the content of protein, minerals, ash, the relations leaf/ stem and NDF/N was better for the one of lower rains (Guayas). It is important to highlight that there were not differences between the varieties for the cell wall components, ADF/N, digestibility and energy contribution that is why their adaptability and potentialities in different ecosystems is confirmed.